Jenis-Jenis Capung (Odonata) di Persawahan Masyarakat Rimbo Tarok Kelurahan Gunung Sarik Kecamatan Kuranji Padang - Saputri, Dilla; Dahelmi, Dahelmi; Safitri, Elza (STKIP PGRI Sumbar, 2013)
ABSTRACT Dragonfly (Odonata) is an insect groups that has medium size to large size, attractive color and it is depended on the waters areas such as in paddy field. The purpose of this study is to know the species of dragonflies found in the paddy fields of Rimbo Tarok of Gunung Sarik Village of Kuranji District, Padang. The samples were collected by using the insect net in morning and evening at three locations: the fields, marshes, and ponds. In this study, four species of dragonflies were found. These are Orthetrum sabina, Crocothemis servilia, Pantala flavescens (belong to Libellulidae family), and Agriocnemis femina (Agriocnidae family).